Local wind speed estimation, with application to wake impingement detection. (February 2018) - Bottasso, C.L.; Cacciola, S.; Schreiber, J.
Abstract: Wind condition awareness is an important factor to maximize power extraction, reduce fatigue loading and increase the power quality of wind turbines and wind power plants. This paper presents a new method for wind speed estimation based on blade load measurements. Starting from the definition of a cone coefficient, which captures the collective zeroth-harmonic of the out-of-plane blade bending moment, a rotor-effective wind speed estimator is introduced. The proposed observer exhibits a performance similar to the well known torque balance estimator. However, while the latter only measures the average wind speed over the whole rotor disk, the proposed approach can also be applied locally, resulting in estimates of the wind speed in different regions of the rotor disk. In the present work, the proposed method is used to estimate the average wind speed over four rotor quadrants. The top and bottom quadrants are used for estimating the vertical shear profile, while the two lateral ones for detecting the presence of a wake shed by an upstream wind turbine. The resulting wake detector can find applicability in wind farm control, by indicating on which side of the rotor the upstream wake is impinging. The new approach is demonstrated with the help of field test data, as well as simulations performed with high-fidelity aeroservoelastic models. Highlights: New method to estimate wind speed based on load measurements, turns the rotor into a wind sensor. Differently from other methods, the present approach can detect local wind speed variations over the rotor disk. Demonstration of the estimation of the vertical wind shear and the impingement of the wake of an upstream wind turbine. Wake detector reliably estimates the wake location, showing promise for its use in wind turbine and wind farm control.